Studi Analisis Kemampuan Lightning Arrester Sebagai Proteksi Transformator Daya pada Gardu Induk Padang Luar ULTG Bukit Tinggi - Yani Ridal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
The substation has very important equipment, namely the transformer, so the transformer must be installed a protection device to minimize interference. These disturbances include overvoltage disturbances due to lightning surges. The protection equipment installed is a lightning arrester that functions to drain overvoltage disturbances caused by lightning strikes directly to the ground, so as not to damage the transformer. This research focuses on substation equipment, namely a tube type lightning arrester with the Siemens brand and has type 3EPG 138-2PF31-2XA1-Z which is connected to a 60 MVA Unindo brand power transformer. Good protection is obtained when the lightning arrester is placed as close as possible to the power transformer terminals. With mathematical calculations for the maximum distance of the line wire length between the lightning arrester and the power transformer is as far as 103.48 meters, while in reality in the field the distance of the line wire length between the lightning arrester and the power transformer at the Padang Luar 150 kV substation is as far as 51 meters, and for the results of the calculation of the maximum distance of the line wire length between the lightning arrester and the power breaker a value of 127.45 meters is obtained, while the distance of the line wire length between the lightning arrester and the power breaker installed at the Padang Luar 150 kV substation is 65 meters